Maximal number of repetitions at percentages of the one repetition maximum: a meta-regression and moderator analysis of sex, age, training status, and exercise - Nuzzo, J. L.; Pinto, M. D.; Nosaka, K.; Steele, J. (Sports Medicine, 2024)
Key Points: